Histopathological lesions of congenital Zika syndrome in newborn squirrel monkeys - de Alcantara, Bianca Nascimento (Sci Rep, 2021)
The absence of an adequate animal model for studies has limited the understanding of congenital Zika syndrome (CZS) in humans during the outbreak in America. In this study, we used squirrel monkeys (Saimiri collinsi), a neotropical primate (which mimics the stages of human pregnancy), as a model of Zika virus (ZIKV) infection. Seven pregnant female squirrel monkeys were experimentally infected at three different gestational stages, and we were able reproduce a broad range of clinical manifestations of ZIKV lesions observed in newborn humans. Histopathological and immunohistochemical analyses of early-infected newborns (2/4) revealed damage to various areas of the brain and ZIKV antigens in the cytoplasm of neurons and glial cells, indicative of CZS. The changes caused by ZIKV infection were intrauterine developmental delay, ventriculomegaly, simplified brain gyri, vascular impairment and neuroprogenitor cell dysfunction. Our data show that the ZIKV infection outcome in squirrel monkeys is similar to that in humans, indicating that this model can be used to help answer questions about the effect of ZIKV infection on neuroembryonic development and the morphological changes induced by CZS.